2004
DOI: 10.1074/jbc.m403417200
|View full text |Cite
|
Sign up to set email alerts
|

La Protein Binding at the GCAC Site Near the Initiator AUG Facilitates the Ribosomal Assembly on the Hepatitis C Virus RNA to Influence Internal Ribosome Entry Site-mediated Translation

Abstract: Translation of hepatitis C virus (HCV) 1 is mediated by an internal ribosome entry site (IRES) located mostly within the 5Ј-untranslated region (UTR) and extending a few nucleotides into the open reading frame (1-5). HCV 5Ј-UTR is highly conserved and folds into a complex secondary structure comprising four major structural domains (I-IV) and a pseudoknot in the vicinity of the initiator AUG codon (6, 7). The cis-elements promote assembly of initiation complex independent of the 5Ј-end and thus mediate interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 38 publications
5
67
0
1
Order By: Relevance
“…For instance, human La supports internal ribosome entry site (IRES)-and cap-dependent translation of viral mRNAs, such as hepatitis C virus, polio virus (Ali et al, 2000;Costa-Mattioli et al, 2004;Pudi et al, 2004), HIV TAR mRNA (Svitkin et al, 1994;Chang et al, 1995), suppresses translation of the hepatitis A virus (Cordes et al, 2008), and regulates IRES-and cap-dependent translation of cellular mRNAs (for example, BiP mRNA , X-linked inhibitor of apoptosis protein (Holcik and Korneluk, 2000), 5 0 TOP-mRNAs (Crosio et al, 2000) and Mdm2 mRNA (Trotta et al, 2003)). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, human La supports internal ribosome entry site (IRES)-and cap-dependent translation of viral mRNAs, such as hepatitis C virus, polio virus (Ali et al, 2000;Costa-Mattioli et al, 2004;Pudi et al, 2004), HIV TAR mRNA (Svitkin et al, 1994;Chang et al, 1995), suppresses translation of the hepatitis A virus (Cordes et al, 2008), and regulates IRES-and cap-dependent translation of cellular mRNAs (for example, BiP mRNA , X-linked inhibitor of apoptosis protein (Holcik and Korneluk, 2000), 5 0 TOP-mRNAs (Crosio et al, 2000) and Mdm2 mRNA (Trotta et al, 2003)). …”
Section: Introductionmentioning
confidence: 99%
“…However, the scope of an siRNA-/shRNA-based antiviral strategy in general is limited because of the evolution of escape mutants. In this study, we purposely targeted the site (nt 331-350) within the SLIV region which encompasses cis-acting elements critical for ribosome assembly and which is likely to be more conserved in the HCV RNA and is protected from the generation of escape variants (Pudi et al, 2004). Thus, the sh-SLIV could be used to achieve broad spectrum inhibition of HCV translation and replication.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have demonstrated the importance of the GCAC sequence near the iAUG for ribosome assembly onto HCV IRES RNA (Pudi et al, 2003(Pudi et al, , 2005. In fact, human La protein (an important host factor) has been shown to bind to the above sites and a peptide derived from the RNA-binding region of La protein has been shown to interfere with the ribosome assembly and inhibit viral RNA translation (Ali et al, 2000;Mondal et al, 2008;Pudi et al, 2004Pudi et al, , 2005. Here, we have investigated the ability of an shRNA targeting this region of HCV IRES to inhibit translation and replication of viral RNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, not much is known about the molecular mechanism by which La facilitates or impairs protein synthesis. Previous work suggested that the La protein might facilitate 48S complex formation during translation initiation of polio virus and hepatitis C virus translation and that La might bind in close proximity to translation start sites [31][32][33][34] . Furthermore, earlier work proposed that the C-terminal domain of La is required to promote polio virus IRES-mediated translation [35] .…”
Section: Research Highlightmentioning
confidence: 99%